Pengaruh Ekstrak Daun Alang Alang (Imperata cylindrica) terhadap Pertumbuhan Tanaman Cabai Merah (Capsicum annum L.) - Alya Putri Alizah; Azwir Anhar (Universitas Cokroaminoto Palopo, 2026)
Red chili peppers (Capsicum annum L.) are an important horticultural commodity with high economic value and play a significant role in meeting people's food needs. However, chili plant productivity often faces constraints due to biotic factors, one of which is interactions with weeds. Cogongrass (Imperata cylindrica) is known as an invasive weed that is generally detrimental, but it contains secondary metabolite compounds that have the potential to be utilized in agriculture. Allelopathic compounds produced by cogongrass can affect the growth of other plants, either inhibitively or stimulatively depending on the concentration and application method. This article aims to examine the potential of cogongrass leaf extract on chili plant growth based on the results of the latest scientific research. The writing method was carried out through a literature review of national and international journals published in 2020 and later. The results of the study indicate that plant extracts, including cogongrass, have the potential to be developed as environmentally friendly natural plant growth regulators, although precise dosage adjustments are required to avoid growth inhibitory effects.